Antiplasmodial, antinociceptive and antipyretic potential of the stem bark extract of Burkea africana and identification of its antiplasmodial-active fraction - Ezenyi, Ifeoma C. (J Tradit Complement Med, 2021)
BACKGROUND AND AIM: Burkea africana stem bark is used as a remedy for malaria in north-central and southern Nigeria. Based on its traditional use, this study was conducted to investigate the antiplasmodial, antinociceptive and antipyretic potential of an extract of B. africana stem bark. EXPERIMENTAL PROCEDURE: A 70% v/v ethanol extract of stem bark of B. africana was prepared by cold maceration. Fractions (dichloromethane, ethyl acetate, and residual) were also prepared. The extract was screened for hemolytic, cytotoxic and antiplasmodial activity effects. The effect of the extract and fractions against chloroquine-sensitive (3D7) and multi-drug resistant (W2mef) P. falciparum was assessed. Acute toxicity test, acetic acid-induced abdominal writhing in mice, and lipopolysaccharide-induced fever in rats were also employed to screen the extract. Chromatographic fingerprints of the extract and active fraction were obtained. RESULTS: B. africana extract showed no cytotoxic or significant hemolytic effects and did not cause acute toxicity or mortality. The ethanol extract exhibited moderate antiplasmodial activity while the dichloromethane fraction showed high activity against P. falciparum 3D7 (IC(50) = 6.44 μg/ml) and W2mef (IC(50) = 6.30 μg/ml) respectively. The extract elicited significant (p < 0.05) attenuation of acetic acid-induced writhing and significantly (p < 0.05) ameliorated lipopolysaccharide-induced pyrexia at 300 mg/kg. The HPLC profile of the dichloromethane fraction showed peaks with retention times that corresponded with those of rutin and caffeic acid. CONCLUSION: Burkea africana extract has antiplasmodial, antinociceptive and antipyretic potential and its antiplasmodial constituents are concentrated in its dichloromethane fraction.